Modulation of IrO6 Chemical Environment for Highly Efficient Oxygen Evolution in Acid. Issue 50 (30th October 2022) - Zhao, Wenli; Xu, Fenghua; Wang, Zhaoyang; Pan, Zhipeng; Ye, Yiming; Hu, Shilin; Weng, Baicheng; Zhu, Rilong
Abstract: The sluggish kinetics of the oxygen evolution reaction (OER) limits the commercialization of oxygen electrochemistry, which plays a key role in renewable energy technologies such as fuel cells and electrolyzers. Herein, a facile and practical strategy is developed to successfully incorporate Ir single atoms into the lattice of transition metal oxides (TMOs). The chemical environment of Ir and its neighboring lattice oxygen is modulated, and the lattice oxygen provides lone‐pair electrons and charge balance to stabilize Ir single atoms, resulting in the enhancement of both OER activity and durability. In particular, Ir0.08 Co2.92 O4 NWs exhibit an excellent mass activity of 1343.1 A g −1 and turnover frequency (TOF) of 0.04 s −1 at overpotentials of 300 mV. And this catalyst also displays significant stability in acid at 10 mA cm −2 over 100 h. Overall water splitting using Pt/C as the hydrogen evolution reaction catalyst and Ir0.08 Co2.92 O4 NWs as the OER catalyst takes only a cell voltage of 1.494 V to achieve 10 mA cm −2 with a perfect stability. This work demonstrates a simple approach to produce highly active and acid‐stable transition metal oxides electrocatalysts with trace Ir. Abstract : A facile strategy to incorporate Ir single atoms into the lattice of transition metal oxides is developed. The chemical environment of Ir and its neighboring oxygen are modulated, resulting in enhanced electrocatalytic oxygen evolution activity and durability. The electrocatalyst exhibits a mass activity of 1343.1 A g −1 and a turnover frequency of 0.04 s −1 .